PELAKSANAAN ANGGARAN PENDAPATAN DAN BELANJA DESA ( APBDESA) DALAM MENUNJANG PEMBANGUNAN DESA DI DESA BETELEN KECAMATAN TOMBATU KABUPATEN MINAHASA TENGGARA - TAMPOMURI, YUNI; RORONG, ARIE; LONDA, VERY (Sam Ratulangi University, 2014)
ABSTRACT :APBDesa ( Income Expenditure Budgeting of Village ) is an explanation needsin building the village as defined in Ministry of Home Affairs Regulation No. 37 Year 2007on Guidelines for village financial management. The aim of this study is to determine theimplementation of village income expenditure to support the rural development in betelenvillage so that the data and information about constraints to the implementation of villageincome expenditure budgeting to supplort the rural development in Betelen village contained.This study uses qualitative research, the simple of informants selected by purposive sampling,sampling technique with particular data source (sugiono 2008). The key informants areselected from five jaga (5 areas) in Betelen village which is consist of village headmen,village secretary, village consultative body chairman, traditional leaders, religious leaders,youth leaders and four communities. A total 15 informants were selected and interviewed..The research results show, that the managerial capacity in financial management of thevillage officials is still lacking, transparency in financial management have not been fullyvisible, there is still confusing in budget management, participation or communityinvolvement in the process of overseeing and providing constructive feedback on theimprovement of financial management has not been fully maximized.